Multistage asymmetric covalent organic framework film and preparation method and application thereof
By designing a multi-stage asymmetric covalent organic frame membrane, the electric field in the membrane promotes cation movement, the problems of degradation of existing membrane selectivity and poor energy harvesting performance are solved, and efficient osmotic energy conversion is achieved.
Patent Information
- Application Number
- CN202510090975.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-01-17
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-21
AI Technical Summary
In practical applications, the existing permeability energy collection membranes are caused by the electrostatic effect of the double layer and the charge screening effect caused by high concentration of counterions, resulting in a decrease in selectivity and poor energy harvesting performance.
A multi-stage asymmetric covalent organic frame film is designed, including a positively charged COF-QA film with a top end, an anodized aluminum film material (AAO) with a macroporous structure in the middle layer, and a negatively charged COF-SO3H film with a bottom end. Through this structure, an electric field is formed in the membrane, which promotes the movement of cations and improves the ion separation efficiency.
The membrane exhibits high selectivity and fast ion transport under a wide range of salinity gradients, reducing energy dissipation and ion concentration polarization effects in the adverse diffusion direction, and improving the output power density of osmotic energy conversion to reach 74.5W m-2.
Smart Images

Figure CN119869241A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a multi-stage asymmetric covalent organic framework membrane and a preparation method and application thereof, in particular to a multi-stage asymmetric COF membrane and a preparation method thereof and application thereof in osmotic energy conversion, belonging to the technical field of osmotic energy conversion. Background Art
[0002] With the growth of global energy demand, it is imperative to develop efficient, renewable and environmentally friendly energy. Among the developed clean energy, the chemical energy existing in the salinity gradient has attracted much attention in recent years due to the ultra-high theoretical energy capacity generated between high-salinity seawater and low-salinity river water. This huge chemical potential energy can be obtained through the reverse electrodialysis (RED) technology, in which ions are driven through the ion exchange membrane under the salinity gradient to generate a net current, so the Gibbs free energy generated by the solution mixing can be directly converted into electrical energy. In the past decade, with the development of materials science and the enrichment of mass transport theory, various materials have been successfully used to harvest osmotic energy. Selective permeable membranes based on graphene oxide, molybdenum disulfide, metal organic frameworks, etc. have shown great potential in osmotic energy harvesting. However, in practical applications, membranes usually show reduced selectivity and poor energy harvesting performance due to the reduced spatial range of the electrostatic effect of the electric double layer (EDL) and the charge screening effect caused by high concentrations of counterions. Therefore, new nanostructure design concepts are urgently needed to promote the further development of high-performance membranes. In the presence of an electric field within the membrane, it promotes the movement of cations in the direction of the electric field, providing an additional driving force for ion separation, and remains effective over a wide range of salt concentrations. Therefore, we designed a multi-stage asymmetric membrane with an inherent field effect to introduce an additional driving force for ion separation, which solves the problem of reduced selectivity in osmotic energy collection and makes it possible to efficiently develop salinity resources. Summary of the invention
[0003] Purpose of the invention: The first purpose of the present invention is to provide a multi-level asymmetric covalent organic framework membrane based on a covalent organic framework. The second purpose of the present invention is to provide a method for preparing the multi-level asymmetric covalent organic framework membrane, which is simple to operate and easy to implement. The third purpose of the present invention is to provide an application of the multi-level asymmetric covalent organic framework membrane in salinity gradient energy conversion. The membrane can be used for salinity gradient energy conversion, extracting osmotic energy from the salinity gradient, and has stable performance, high conversion power, and still maintains excellent output under a wide salinity gradient.
[0004] Technical solution: The present invention discloses a multi-level asymmetric covalent organic framework membrane, which includes a three-layer structure, wherein the top layer is a positively charged COF-QA membrane, the middle layer is an anodized aluminum membrane material (AAO) with a macroporous structure, and the bottom layer is a negatively charged COF-SO3H membrane, and some pores of the COF-QA membrane and some pores of the COF-SO3H membrane correspond to and communicate with some macropores in the anodized aluminum membrane material with a macroporous structure.
[0005] Furthermore, the thickness of the positively charged COF-QA membrane is 100 to 110 nm, preferably 106 nm, and the pore size of the positively charged COF-QA membrane is 2 to 2.4 nm, preferably 2.3 nm.
[0006] Furthermore, the thickness of the negatively charged COF-SO3H film is 102-107 nm, preferably 100 nm, and the pore size of the negatively charged COF-SO3H film is 1.7-1.9 nm, preferably 1.8 nm.
[0007] Furthermore, the pore diameter of the macroporous anodized aluminum film material is 50 to 80 nm, preferably 70 nm.
[0008] Furthermore, the zeta potential of the positively charged COF-QA film is 16 to 19 mv, preferably 18 mv.
[0009] Furthermore, the zeta potential of the negatively charged COF-SO3H film is -36 to -39 mv, preferably -38 mv.
[0010] The method for preparing the multi-level asymmetric covalent organic framework membrane of the present invention comprises the following steps:
[0011] (1) Anodized aluminum oxide is sandwiched in an H-type electrolytic cell, 1,3,5-triaminophenylbenzene (TAPB) solution and 2,5-dihydroxy-1,4-benzenedicarbaldehyde (DHBDA) solution are added to both chambers of the electrolytic cell, a catalyst is added, and a Schiff base reaction is performed to obtain a DT / AAO / DT membrane;
[0012] (2) adding 3-bromopropyltrimethylammonium bromide solution and 3-bromopropyl sodium sulfonate solution to both sides of the H-type electrolytic cell, respectively, and reacting with Williamson ether to obtain a QA / AAO / SO3H membrane;
[0013] (3) The QA / AAO / SO3H membrane is taken out, washed with a solvent, and vacuum dried to obtain a multi-level asymmetric covalent organic framework membrane.
[0014] Furthermore, in step (1), the solvent used in the preparation of the TAPB solution and the DHBDA solution is a mixed solution of 1,4-dioxane and mesitylene in a volume ratio of 4:1.
[0015] Furthermore, in step (2), the solvent used in the preparation of the 3-bromopropyltrimethylammonium bromide solution and the 3-bromopropyl sodium sulfonate solution is N,N-dimethylformamide.
[0016] Furthermore, in step (1), the concentration of the TAPB solution is 0.02 to 0.02 mmol / mL, preferably 0.02 mmol / mL, and the concentration of the DHBDA solution is 0.015 to 0.03 mmol / mL, preferably 0.03 mmol / mL.
[0017] Furthermore, in step (1), the catalyst is glacial acetic acid.
[0018] Furthermore, in step (1), the temperature of the Schiff base reaction is 50 to 70° C., preferably 70° C., and the time of the Schiff base reaction is 48 to 60 h, preferably 48 h.
[0019] Furthermore, in step (2), the concentrations of the 3-bromopropyltrimethylammonium bromide solution and the 3-bromopropyl sodium sulfonate solution are both 0.8 to 1 mol / L, preferably 1 mol / L.
[0020] Furthermore, in step (2), the temperature of the Williamson ether reaction is 80 to 100° C., preferably 100° C., and the time of the Williamson ether reaction is 12 to 30 hours, preferably 24 hours.
[0021] Furthermore, in step (3), the solvent is tetrahydrofuran.
[0022] Furthermore, in step (3), the vacuum drying temperature is 80 to 100° C., preferably 80° C., and the vacuum drying time is 12 to 24 h, preferably 12 h.
[0023] Application of the multi-level asymmetric covalent organic framework membrane in the salinity gradient energy conversion process.
[0024] Furthermore, during the application process, a salinity difference is formed between the concentrated salt solution and the dilute salt solution, and the salt difference energy is converted into electrical energy.
[0025] Furthermore, the molar concentration ratio of the concentrated salt solution to the dilute salt solution is (0.5-5):0.01.
[0026] Furthermore, the molar concentration of the concentrated salt solution is 0.5 to 5 mol / L.
[0027] Furthermore, the molar concentration of the dilute salt solution is 0.01 mol / L.
[0028] Furthermore, the concentrated salt solution and the dilute salt solution have the same salt type.
[0029] Furthermore, the concentrated salt solution and the dilute salt solution are both sodium chloride solutions.
[0030] The present invention firstly adopts an in-situ growth method to grow COF-DT membranes on both sides of AAO, and then grafts sulfonate and quaternary ammonium salt groups with different electrical properties on both sides to obtain the membrane. The COF layers on both sides have high porosity and regular and orderly pore arrangement. The high porosity and orderly pore arrangement of COF ensure high ion flux in osmotic energy collection. Due to the superiority of the multi-level asymmetric structure, it exhibits a higher rectification response, thereby reducing the Joule heat induced energy dissipation and ion concentration polarization (ICP) effect in the unfavorable diffusion direction. In addition, the COF membrane materials on both sides carry opposite charges, and there is an electric field in the membrane pointing from the COF-QA side to the COF-SO3H side. The electric field promotes the movement of cations along the direction of the electric field, provides additional driving force for ion separation, and remains effective in a wide range of salt concentrations. The output power density of the multi-level asymmetric membrane can reach 74.5W m at a salinity gradient of 500 times. -2 In summary, the multi-level asymmetric membrane constructed by COF for osmotic energy conversion can obtain extremely excellent output power and has broad application prospects.
[0031] The multi-level asymmetric covalent organic framework membrane designed by the present invention realizes high selectivity and rapid ion transport. Compared with the traditional heterogeneous membrane, the multi-layer asymmetric structure has a stronger rectification ratio, which reduces the energy dissipation and ion concentration polarization (ICP) effect in the unfavorable diffusion direction caused by Joule heating. In addition, in a neutral solution, the surfaces of the COF-QA membrane and the COF-SO3H membrane are positively charged and negatively charged, respectively, and a potential difference is formed in the membrane, which promotes the migration of cations in the direction of COF-SO3H and hinders the migration of anions in the direction of COF-SO3H. The asymmetric structure and asymmetric surface charge distribution of the multi-level asymmetric membrane enhance ion charge separation, accelerate cation transport, and are effective in a wide range of salinity, thereby improving energy collection performance.
[0032] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0033] (1) The multi-level asymmetric covalent organic framework membrane of the present invention comprises a COF-QA membrane with a positive charge on the top, an anodic aluminum oxide membrane material (AAO) with a macroporous structure in the middle, and a negatively charged COF-SO3H membrane at the bottom. The preparation method is simple and convenient, and the reaction conditions are easy to achieve.
[0034] (2) The application of the multi-stage asymmetric covalent organic framework membrane of the present invention in salinity gradient osmotic energy conversion has obvious advantages:
[0035] First, COF materials have ordered nanochannels, ultra-high porosity, and adjustable surface properties. Ordered nanochannels and high porosity lay the foundation for fast ion transport and high ion flux. Adjustable surface properties allow different functional groups to be directly attached along the pore wall, providing feasibility for the preparation of osmotic energy collection materials with different properties.
[0036] Secondly, the inherent structural asymmetry of the multi-level asymmetric covalent organic framework membrane greatly improves the ion current rectification characteristics compared with traditional heterogeneous membranes, combining the strong confinement effect of the cavity. This reduces the energy dissipation in the unfavorable diffusion direction caused by Joule heating and the ion concentration polarization (ICP) effect.
[0037] At the same time, due to the asymmetric charge distribution of the multi-level asymmetric covalent organic framework membrane, in a neutral solution, the surfaces of COF-QA and COF-SO3H are positively and negatively charged, respectively, forming a potential difference in the membrane. The asymmetric surface charge distribution enhances ionic charge separation, accelerates cation transport, and improves energy collection performance.
[0038] Again, the multi-stage asymmetric covalent organic framework membrane of the present invention successfully converted salinity gradient energy into electrical energy in the salinity gradient osmotic energy conversion. Under the conditions of simulating the salinity gradient of seawater (0.5 mol / L NaCl) and river water (0.01 mol / L NaCl), the maximum output power density reached 9.5 W m -2 , this is the commercial standard 5W m -2 Above that, further increasing the salinity gradient (5mol / L NaCl / 0.01mol / L NaCl), the maximum output power density can be increased to 74.5Wm -2 .
[0039] Finally, the present invention can support the normal operation of the timer under the condition of connecting ten 50-fold NaCl salinity gradient electrolytic cells in series, confirming the excellent application potential of the multi-stage asymmetric covalent organic framework membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 A schematic diagram of the preparation process of the multi-level asymmetric covalent organic framework membrane prepared in Example 1;
[0041] Figure 2 Schematic diagram of the preparation process of the AAO membrane in Example 1;
[0042] Figure 3 is a scanning electron microscope image of the AAO film prepared in Example 1;
[0043] Figure 4 This is a scanning electron microscope image of the multi-level asymmetric covalent organic framework membrane prepared in Example 1;
[0044] Figure 5 This is a schematic diagram of the salinity gradient osmotic energy conversion device in Example 2;
[0045] Figure 6 The current density and external resistance relationship diagram and the power density and external resistance relationship diagram obtained in the different salinity gradient osmotic energy conversion of the multi-stage asymmetric covalent organic framework membrane in Example 2;
[0046] Figure 7 This is a graph of the osmotic energy conversion efficiency of the multi-level asymmetric covalent organic framework membrane prepared in Example 1 under different salinity gradients;
[0047] Figure 8 The relationship between power density and external resistance of the multi-stage asymmetric membrane with different grafting times prepared in Example 2 under 0.01 mol / L: 5 mol / L NaCl gradient;
[0048] Fig. 9 A comparison chart of the output power density of the multi-level asymmetric covalent organic framework membrane prepared in Example 1 and the QA / AAO and SO3H / AAO prepared in Comparative Examples 1-2 under a 0.01 mol / L: 5 mol / L NaCl gradient;
[0049] Fig.10 It is a comparison diagram of the penetration energy collection power density in Example 1 and Comparative Example 3;
[0050] Fig.11 The salinity gradient permeability energy conversion test diagram of the covalent organic framework multi-level asymmetric membrane in Example 3 within 8 days; (A) the relationship between current density and external resistance, (B) the relationship between power density and external resistance;
[0051] Fig.12 This is a diagram of the covalent organic framework multi-level asymmetric membrane powering the timer in Example 1. DETAILED DESCRIPTION
[0052] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0053] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources. Example 1 Preparation of multi-level asymmetric covalent organic framework membrane
[0054] (1) Preparation of anodic aluminum oxide (AAO) film:
[0055] First, the aluminum foil needs to be ultrasonically cleaned with anhydrous ethanol and 1 mol / L KOH solution for 15 minutes respectively, and then deionized water is used to thoroughly rinse off the residual liquid on the surface of the aluminum foil. The initial anodization process uses 0.3 mol / L oxalic acid as the electrolyte and lasts for 30 minutes under constant conditions of 40V voltage and 25°C. Next, the oxide layer formed on the surface of the aluminum foil after the initial anodization is cleaned at 60°C for 40 minutes using an acidic solution mixed with 5wt% phosphoric acid and 1.5wt% oxalic acid. After that, a second anodization is carried out for 6 hours, and the other conditions remain the same as the initial anodization. Subsequently, a saturated SnCl2 solution is used to remove the aluminum substrate. Next, the AAO membrane is treated with a 5wt% phosphoric acid solution for 60 minutes to remove the barrier layer on the top of the anodized aluminum membrane. The entire preparation process is as follows. Figure 2 shown.
[0056] Next, the prepared AAO membrane was immersed in a 30% hydrogen peroxide solution and boiled at 95°C for 30 minutes to modify the channel surface with abundant hydroxyl groups. Finally, the AAO membrane was soaked in deionized water overnight and dried. By adjusting the voltage during the anodization process, the pore size of the anodized aluminum membrane nanochannel can be effectively controlled. After scanning electron microscopy analysis of the AAO membrane, the results showed that its pore size was 70nm and the pores were evenly distributed, such as Figure 3 shown.
[0057] (2) Preparation of covalent organic framework multi-level asymmetric membranes:
[0058] First, a mixed solution of anhydrous 1,4-dioxane and mesitylene (v:v=4:1) was prepared, and then the mixed solution was prepared into TAPB solution and DHBDA solution with concentrations of 0.02mmol / L and 0.03mmol / L, respectively. The AAO prepared in Example 1(1) was placed in an H-type electrolytic cell, 5mL of TAPB and DHBDA solutions were added to both chambers, 200μL of anhydrous acetic acid was added as a catalyst, and the reaction was carried out at 70℃ for 48h. The DT / AAO / DT membrane was obtained. 1mol / L 3-bromopropyltrimethylammonium bromide solution and 3-bromopropane sodium sulfonate solution were prepared with N,N-dimethylformamide as solvent, and the concentrations were both 1mol / L. 10mL of 3-bromopropyltrimethylammonium bromide and 3-bromopropane sodium sulfonate were added to both sides of the DT / AAO / DT membrane, respectively, and the reaction was carried out at 100℃ for 24h to obtain the QA / AAO / SO3H membrane. The QA / AAO / SO3H membrane material obtained above was taken out, washed with tetrahydrofuran solvent, and vacuum dried at 80°C for 12 hours to obtain a multi-level asymmetric covalent organic framework membrane. Figure 1 shown.
[0059] The multi-level asymmetric covalent organic framework membrane prepared in this example was analyzed by scanning electron microscopy. Figure 4 shown. Figure 4 The scanning electron microscope images of the multi-level asymmetric covalent organic framework membrane prepared in Example 1, wherein (A) is a cross-sectional image of the multi-level asymmetric covalent organic framework membrane. (B) is a side cross-sectional image of the multi-level asymmetric covalent organic framework membrane COF-SO3H. (C) is a side cross-sectional image of the multi-level asymmetric covalent organic framework membrane COF-QA. (D) is a side planar image of the multi-level asymmetric covalent organic framework membrane COF-SO3H. (E) is a side planar image of the multi-level asymmetric covalent organic framework membrane COF-QA. Figure 4 It can be seen that both sides of the membrane have dense and defect-free COF films with a thickness of about 100 nm. These results confirm the formation of a double-sided asymmetric structure on the AAO substrate.
[0060] Example 2 Preparation of multi-stage asymmetric membranes with different grafting times
[0061] The preparation process was the same as that in Example 1, except that the reaction time after adding 10 mL of 3-bromopropyltrimethylammonium bromide and 3-bromopropyl sodium sulfonate to both sides of the DT / AAO / DT membrane in step (2) of Example 1 was changed to 12 h, 18 h, and 30 h, respectively.
[0062] Example 3 Application of salinity gradient osmotic energy conversion of multi-stage asymmetric covalent organic framework membrane
[0063] 1. Salinity gradient osmotic energy conversion device such as Figure 5 As shown, the salinity gradient osmosis energy conversion device is a H-two-chamber electrochemical electrolytic cell, and the multi-stage asymmetric covalent organic framework membrane prepared in Example 1 is fixed in the middle of the two cells. A concentrated salt solution (0.5-5 mol / L NaCl electrolyte solution) is installed on the COF-QA side, and a dilute salt solution (0.01 mol / L NaCl electrolyte solution) is installed on the COF-SO3H side. The two salt solutions are connected to the circuit through an external electrochemical workstation and a load resistor. By adjusting the change in the external resistance value, the measurement of the relationship curve between the current density, power density and external resistance is achieved. The results are shown in FIG. Figure 6 shown.
[0064] Figure 6 The current density, power density and external resistance relationship diagrams obtained in the different salinity gradient osmotic energy conversion of the salinity multi-level asymmetric covalent organic framework membrane in Example 3, wherein (A) is the current density and external resistance relationship diagram, and (B) is the power density and external resistance relationship diagram. Figure 6 It can be seen that under the 0.01mol / L:0.5mol / L NaCl gradient, the corresponding external circuit power density is 9.5W m -2, meeting the commercial standard of 5W m -2 At 0.01mol / L:5mol / L NaCl, the power density reaches 74.5W m -2 .like Figure 7 As shown, the energy conversion efficiency of the multi-level asymmetric covalent organic framework membrane in Example 1 reaches 34% at high salt concentration, which indicates the superiority of the multi-level asymmetric covalent organic framework membrane in the osmotic energy collection performance at high salt concentration.
[0065] 2. Permeation energy collection of multi-stage asymmetric covalent organic framework membranes with different grafting times
[0066] The salinity gradient osmotic energy conversion device in step 1 was used, and the composite membranes in the salinity gradient osmotic energy conversion device were replaced by the multi-stage asymmetric covalent organic framework membranes prepared in Example 2. Other conditions remained unchanged, and the effect of changing the grafting group time on the salinity gradient osmotic energy conversion performance was studied. The results are as follows: Figure 8 shown.
[0067] Figure 8 The power density and external resistance relationship diagram obtained from the salinity gradient osmotic energy conversion of the multi-stage asymmetric covalent organic framework membrane with different grafting times in Example 1 and Example 2 is shown in FIG. Figure 7 It can be found that when the grafting time is 12h, 18h, 24h, and 30h, respectively, under the gradient of 0.01mol / L:5mol / L NaCl, the corresponding external circuit power density is 39.3Wm -2 、58.4W m -2 、74.5W m -2 and 42.1W m -2 When the grafting time is 24h, the salinity gradient osmotic energy conversion output power is the highest.
[0068] Comparative Example 1
[0069] Preparation of QA / AAO membrane: The preparation process is the same as that of Example 1, except that the AAO in Example 1 is placed in parallel in a common reaction bottle, and the COF membrane is grown only on one side of the AAO. After obtaining DT / AAO, 10 mL of 1 mol / L 3-bromopropyltrimethylammonium bromide solution prepared with N, N-dimethylformamide as solvent is added, and the reaction is carried out at 100°C for 24 hours. The above composite membrane material is taken out, washed with tetrahydrofuran solvent, and vacuum dried at 80°C for 12 hours to obtain the QA / AAO membrane.
[0070] Comparative Example 2
[0071] Preparation of SO3H / AAO membrane: The preparation of QA / AAO membrane is the same as that of QA / AAO membrane, except that 1 mol / L 3-bromopropyltrimethylammonium bromide solution is replaced by 1 mol / L 3-bromopropyl sodium sulfonate solution to obtain SO3H / AAO membrane.
[0072] The QA / AAO membrane and SO3H / AAO membrane prepared in Comparative Example 1 and Comparative Example 2 were subjected to salinity gradient osmotic energy conversion application. The experimental process was the same as in Example 2. The results are as follows: Figure 8 shown.
[0073] Depend on Fig. 9 The experimental results show that the output power density of the multi-stage asymmetric membrane QA / AAO / SO3H prepared in Example 1 is much higher than that of QA / AAO prepared in Comparative Example 1 and SO3H / AAO prepared in Comparative Example 2 under the concentration gradient of 0.01mol / L:5mol / L NaCl. The corresponding external circuit power density of QA / AAO and SO3H / AAO under the gradient of 0.01mol / L:5mol / L NaCl is 28.8Wm -2 and 34.6W m -2 , which is far lower than the external circuit power density of the multi-stage asymmetric membrane QA / AAO / SO3H of the present invention. The asymmetric structure and asymmetric surface charge distribution of the multi-stage asymmetric membrane enhance ion charge separation, accelerate cation transport, and are effective in a wide salinity range, thereby improving energy collection performance.
[0074] Comparative Example 3
[0075] The existing asymmetric membranes ZIF-8-AAO-WO3 (see Fu, Y. Wang, J. Jiang, B. Lu, J. Zhai, ACS Applied Materials & Interfaces 2021, 13, 35197-35206.), J-MOF (see Z.-Q. Li, G.-L. Zhu, R.-J. Mo, M.-Y. Wu, X.-L. Ding, L.-Q. Huang, Z.-Q. Wu, X.-H. Xia, ACS Applied Materials & Interfaces 2023, 15, 23922-23930) and MC / AAO / MS (see S. Zhou, L. Xie, X. Zhang, M. Yan, H. Zeng, K. Liang, L. Jiang, B. Kong, Advanced Materials & Interfaces 2023, 15, 23922-23930) with similar structures to ours were analyzed. The salinity gradient osmotic energy conversion output power density of the multi-stage asymmetric membrane in Example 1 is compared with the salinity gradient osmotic energy collection performance. The results are as follows Fig.10 shown. Fig.10This is a comparison chart of the maximum output power density obtained by the multi-stage asymmetric membrane in Example 1 and the existing membrane material in Comparative Example 3 in 0.01mol / L:0.5mol / L NaCl salinity gradient osmotic energy conversion. Fig.10 The comparison results show that the permeation energy collection performance of the multi-level asymmetric covalent organic framework membrane prepared in Example 1 is much higher than that of other membranes.
[0076] Example 3 Stability test of salinity gradient osmotic energy conversion of multi-stage asymmetric membrane
[0077] The multi-stage asymmetric covalent organic framework membrane in Example 1 was placed for 0 days, 2 days, 4 days, 6 days, and 8 days to conduct salinity gradient osmotic energy conversion tests. The results are as follows Fig.11 Example 1 Preparation of multi-level asymmetric covalent organic framework membranes in salinity gradient osmotic energy conversion applications showed good stability, after 8 consecutive days of testing, the output power density decreased by less than 5%, laying a reliable foundation for subsequent practical applications.
[0078] Example 4 Practical application of multi-level asymmetric covalent organic framework membrane
[0079] The multi-stage asymmetric covalent organic framework membrane in Example 1 was used to construct a series generator. When ten electrolytic cells of 0.01 mol / L: 0.5 mol / L NaCl were connected in series, Fig.12 The output voltage shown reached 1.43V, which can support the normal operation of the timer, further confirming the excellent application potential of the multi-level asymmetric membrane.
Claims
1. A multi-level asymmetric covalent organic framework membrane, characterized in that: The multi-level asymmetric covalent organic framework membrane includes a three-layer structure, wherein the top layer is a positively charged COF-QA membrane, the middle layer is an anodized aluminum membrane material with a macroporous structure, and the bottom layer is a negatively charged COF-SO3H membrane. Some pores of the COF-QA membrane and some pores of the COF-SO3H membrane correspond to and communicate with some macropores in the anodized aluminum membrane material with a macroporous structure.
2. The multi-level asymmetric covalent organic framework membrane according to claim 1, characterized in that: The thickness of the COF-QA membrane is 100-110 nm, the pore size of the COF-QA membrane is 2-2.4 nm, the thickness of the COF-SO3H membrane is 102-107 nm, the pore size of the COF-SO3H membrane is 1.7-1.9 nm, and the pore diameter of the macroporous anodized aluminum membrane material is 50-80 nm.
3. The method for preparing the multi-stage asymmetric covalent organic framework membrane according to claim 1 or 2, characterized in that: The steps include: (1) Anodized aluminum oxide is sandwiched in an H-type electrolytic cell, 1,3,5-triaminophenylbenzene solution and 2,5-dihydroxy-1,4-benzenedicarbaldehyde solution are added to two chambers of the electrolytic cell, a catalyst is added, and a DT / AAO / DT membrane is obtained through a Schiff base reaction; (2) adding 3-bromopropyltrimethylammonium bromide solution and 3-bromopropyl sodium sulfonate solution to both sides of the H-type electrolytic cell, respectively, and reacting with Williamson ether to obtain QA / AAO / SO3H membrane; (3) The QA / AAO / SO3H membrane is taken out, washed with a solvent, and vacuum dried to obtain a multi-level asymmetric covalent organic framework membrane.
4. The preparation method according to claim 3, characterized in that: In step (1), the solvent used in the configuration of 1,3,5-triaminophenylbenzene solution and 2,5-dihydroxy-1,4-benzenedicarbaldehyde solution is a mixed solution of 1,4-dioxane and mesitylene in a volume ratio of 4:
1. In step (2), the solvent used in the configuration of 3-bromopropyltrimethylammonium bromide solution and 3-bromopropyl sodium sulfonate solution is N,N-dimethylformamide.
5. The preparation method according to claim 3, characterized in that: In step (1), the concentration of the 1,3,5-triaminophenylbenzene solution is 0.02 to 0.02 mmol / mL, and the concentration of the 2,5-dihydroxy-1,4-benzenedicarbaldehyde solution is 0.015 to 0.03 mmol / mL.
6. The preparation method according to claim 3, characterized in that: In step (1), the catalyst is glacial acetic acid, the temperature of the Schiff base reaction is 50 to 70° C., and the time of the Schiff base reaction is 48 to 60 hours.
7. The preparation method according to claim 3, characterized in that: In step (2), the concentrations of the 3-bromopropyltrimethylammonium bromide solution and the 3-bromopropyl sodium sulfonate solution are both 0.8 to 1 mol / L, the temperature of the Williamson ether reaction is 80 to 100° C., and the reaction time of the Williamson ether is 12 to 30 h.
8. The preparation method according to claim 3, characterized in that: In step (3), the solvent is tetrahydrofuran, the vacuum drying temperature is 80 to 100° C., and the vacuum drying time is 12 to 24 hours.
9. Use of the multi-stage asymmetric covalent organic framework membrane according to claim 1 or 2 in a salinity gradient energy conversion process.
10. The use according to claim 9, characterized in that: During the application process, the concentrated salt solution and the dilute salt solution form a salinity difference, and the salt difference energy is converted into electrical energy. Among them, the molar concentration ratio of the concentrated salt solution to the dilute salt solution is (0.5-5): 0.01, the concentrated salt solution and the dilute salt solution are both sodium chloride solutions.
Citation Information
Patent Citations
Preparation method and application of nanofiltration composite membrane
CN115715936A
COFs modified AAO membrane, preparation method thereof and sodium ion battery
CN115863924A
COF / Au / AAO nanofluid hybrid membrane as well as preparation method and application thereof
CN118142360A
Ionic type conjugated microporous polymer nano-channel composite membrane as well as preparation method and application thereof
CN118756155A
Double-layer covalent organic framework composite ion exchange membrane and preparation method thereof
CN118919788A